2019
DOI: 10.3389/fpsyt.2019.00336
|View full text |Cite
|
Sign up to set email alerts
|

Internet Gaming Disorder in Adolescents With Psychiatric Disorder: Two Case Reports Using a Developmental Framework

Abstract: Internet gaming disorder (IGD) has been a controversial entity with various opinions about its clinical relevance as an independent mental disorder. This debate has also included discussions about the relationships between problematic gaming, various psychiatric disorders, and personality traits and dimensions. This paper outlines a developmental-theory based model of Internet gaming misuse inspired by the treatment of two adolescent inpatients. The two clinical vignettes illustrate distinct developmental path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 55 publications
0
21
0
Order By: Relevance
“…Additionally, parental physical abuse has been reported to be associated with problematic gaming in adolescents (60). Children who are exposed to abusive nurturing practices are likely to develop both internalizing and externalizing (62) symptoms which, in turn, have been demonstrated to be susceptibility factors for IGD (63).…”
Section: Childhood Maltreatmentmentioning
confidence: 99%
“…Additionally, parental physical abuse has been reported to be associated with problematic gaming in adolescents (60). Children who are exposed to abusive nurturing practices are likely to develop both internalizing and externalizing (62) symptoms which, in turn, have been demonstrated to be susceptibility factors for IGD (63).…”
Section: Childhood Maltreatmentmentioning
confidence: 99%
“…Refs. (18, 26)]. Benarous and colleagues, for instance, describe how avoidance and social withdrawal as a persistent maladaptive reaction in a patient with an anxious–avoidant insecure attachment plays a key role in the emergence and persistence of Internet gaming disorder.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Recently, two of these pathways have been indirectly adapted to explain the development of gaming disorder. Based on case reports, Benarous et al (2019) identified an "internalized pathway" (involving depressive symptoms during adolescence) and an "externalized pathway" (involving conduct problems during adolescence) towards the development of gaming disorder in young adulthood. Indeed, subtypes of problem gamers have been identified depicting greater aggressive and/or depressive symptoms (Lemmens, Valkenburg, & Gentile, 2015;Myrseth & Notelaers, 2018;Sanders & Williams, 2019;Yu & Cho, 2016), with longitudinal studies identifying the predictive role of greater internalizing and externalizing symptoms for problem gaming (Krossbakken et al, 2018;Liu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%